Effects of total glucosides of paeony on serum inflammatory cytokines in animal models of rheumatoid arthritis: a systematic review and meta-analysis - He, Mengdi; Hu, Zhipeng; Yang, Maoyi (Frontiers in Pharmacology, 2024)
Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic synovitis of the affected joints. Total glucosides of paeony (TGP) capsules have been widely used clinically for the treatment of RA with good efficacy and safety. However, its effect on inflammatory cytokines remains unclear. Objectives: This study aimed to summarize the effect of TGP on the expression level of serum inflammatory cytokines in RA animal models and its potential mechanisms. Methods: Six databases were searched up to August 14, 2023, relevant animal experiment studies were screened, data were extracted, and the SYRCLE animal experiment bias risk assessment tool was used for risk assessment. Results: A total of 24 studies were included, including 581 animals. Results showed that compared with the model control group, TGP decreased the levels of TNF-α, IL-1β, IL-6, and PGE2 and increased the levels of TGF-β1 after 1 to 2 weeks of intervention, decreased the levels of TNF-α, IL-1β, IL-6, IL-2, IL-17, IL-17α, IL-21, VEGF, IFN-γ and PGE2 and increased the levels of IL-10 and IL-4 after 3 to 4 weeks of intervention, decreased the levels of TNF-α, IL-6, IL-17α and increased the level of IL-10 after 8 weeks of intervention. There was no significant difference in the effects of TGP on the levels of IL-10, IL-17, and IFN-γ after 1 to 2 weeks of intervention and IL-1 and TGF-β1 after 3 to 4 weeks of intervention. Conclusion: In summary, based on the existing studies, this study found that compared with the control group of the RA animal model, TGP can reduce the levels of serum pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 and increase the levels of serum anti-inflammatory cytokines such as IL-10, exerting an antiinflammatory effect by regulating and improving the levels of inflammatory cytokines, and thus alleviating the disease. Given the low quality of the included studies and the lack of sufficient evidence, more high-quality studies are still needed to validate the results of this study.